Pregnancy, Childbirth, and Primary Care-Givers in Ancient Rome - Scarfo, Barbara Nancy (My University, 2020)
This thesis presents the array of evidence concerning three crucial aspects of Roman maternity: pregnancy, childbirth, and primary care-givers. I explore how these elements of maternity are represented in the ancient sources and observe how the evidence corresponds to and diverges from the established impressions of these facets of maternity. I consider several issues surrounding the critical, initial moments of the life-cycle and how they are informed by biological factors, social structures, and cultural projections. Motherhood and childhood at Rome have garnered a great deal of interest, but issues of conception, gestation, childbirth, and early infant care have received much less attention. In this thesis they are considered together and thus in light of one another. The first chapter of this study surveys the social context of Roman maternity through an examination of the purpose of an extensive reproductive period, its associated problems, and the impact that such a practice had on Roman attitudes towards pregnancy and childbirth. The second and third chapters of this study are dedicated to an examination of the social and cultural identity of the two slaves who provided crucial functions throughout the pregnancy, delivery, and post-natal care of the Roman mother and child: the obstetrix (midwife) and the nutrix (wet-nurse). The final chapter shifts the focus from couples who sought to create a Roman family of their own to those who chose to limit the size of their families through contraception, abortion, infanticide, or infant exposure. I examine the attitudes towards these methods of family limitation and the critical role that parental intent had in the formation of these perceptions. By drawing on a range of ancient material, chief among which are medical writers, jurists, and funerary inscriptions, I argue that social status and demographic realities, such as high maternal and infant mortality rates, played equally significant roles in these central aspects of Roman maternity, and indeed influenced one another.
Keywords: Classics; Rome; Maternity; Social Status; Demography; Roman Slavery; Roman Family